2008
DOI: 10.1103/physreva.78.022509
|View full text |Cite
|
Sign up to set email alerts
|

Autoionizing Rydberg series(np,nf)of Ar investigated by stepwise excitations with lasers and synchrotron radiation

Abstract: Synchrotron radiation is used to excite Ar to the intermediate states 3p 1/2 5 ͑3dЈ͓3 / 2͔ 1 , 5dЈ͓3 / 2͔ 1 , 5sЈ͓1 / 2͔ 1 , 7sЈ͓1 / 2͔ 1 ͒ and 3p 3/2 5 ͑6d͓1 / 2͔ 1 , 6d͓3 / 2͔ 1 , 8s͓3 / 2͔ 1 ͒, then excited by lasers to the autoionizing Rydberg series 3p 1/2 5 npЈ ͓͑1 / 2͔ 0,1 , ͓3 / 2͔ 1,2 ͒ and nfЈ͓5 / 2͔ 2. For the intermediate states of 5sЈ, 7sЈ, and 8s, the npЈ ͓͑1 / 2͔ 0 and ͓3 / 2͔ 2 ͒ series are observed with high intensity but not the npЈ ͓͑1 / 2͔ 1 and ͓3 / 2͔ 1 ͒ series when the polarization vect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 39 publications
2
30
0
Order By: Relevance
“…The 7s [1/2] 1 and 8s[3/2] 1 levels (energetic separation of only 6.6 meV) are strongly mixed by configuration interaction. When this interaction is taken into account the calculated spectra for these intermediate levels exhibit lineshapes in satisfactory agreement with the experimental data of Lee et al (2008). The np ARS excited from 4s [1/2] and 5s[3/2] are strongly influenced by the fact that the J = 1 and J = 2 amplitudes are near zero (i.e., are close to a Seaton-Cooper minimum).…”
Section: Introductionsupporting
confidence: 77%
See 3 more Smart Citations
“…The 7s [1/2] 1 and 8s[3/2] 1 levels (energetic separation of only 6.6 meV) are strongly mixed by configuration interaction. When this interaction is taken into account the calculated spectra for these intermediate levels exhibit lineshapes in satisfactory agreement with the experimental data of Lee et al (2008). The np ARS excited from 4s [1/2] and 5s[3/2] are strongly influenced by the fact that the J = 1 and J = 2 amplitudes are near zero (i.e., are close to a Seaton-Cooper minimum).…”
Section: Introductionsupporting
confidence: 77%
“…Over the past few years, two-photon excitation studies of ground state Ne (Petrov et al 2006b) and Ar (Lee et al 2008) atoms via several short-lived intermediate, odd-parity J = 1 levels as well as one-photon excitation from the respective mp 5 (m + 1)s, J = 2, 0 metastable levels (Peters et al 2005, Petrov et al 2006a, Wright et al 2008 yielded new results on the lineshapes of the even-parity np J = 0, 1, 2 and nf J = 2 ARS the proper description of which poses a substantial challenge to theory. Calculations of the shapes, widths and energy positions of the Ne(np ) ARS by means of the configuration-interaction Pauli-Fock core-polarization (CIPFCP) method (see, e.g., Peters et al 2005, Petrov et al 2006a, 2009 were found to be in good overall agreement with experimental results (Petrov et al 2006b) only after proper inclusion of an interference effect between the direct 3s|r|np and the intershell 3s|r|3p 3p|V (2p2p)|np amplitudes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only low angular momentum states that decay very quickly (picosecond-to-nanosecond time scale) by radiationless autoionization through a core spin flip due to the Rydberg electron-core interaction would be accessible. These autoionizing states (primarily s , p , and d states) in Ar and other noble gases have been studied extensively over many years, primarily through single-and multiphoton highresolution spectroscopy where the linewidth of the observed resonances can be used to extract the lifetime of the states [8][9][10][11][12][13][14][15]. Experimental studies of these low-l states have been compared to theoretical calculations to better understand the dynamics of autoionization [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%